Genome-wide mega-analysis identifies 16 loci and highlights diverse biological mechanisms in the common epilepsies - The International League Against Epilepsy Consortium on Complex Epilepsies (Nature Portfolio, 2018)
Epilepsies are common brain disorders and are classified based on clinical phenotyping, imaging and genetics. Here, the authors perform genome-wide association studies for 3 broad and 7 subtypes of epilepsy and identify 16 loci - 11 novel - that are further annotated by eQTL and partitioned heritability analyses.